2017
DOI: 10.1136/bjsports-2017-098005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a movement control injury prevention programme in adult men’s community rugby union: a cluster randomised controlled trial

Abstract: BackgroundExercise programmes aimed at reducing injury have been shown to be efficacious for some non-collision sports, but evidence in adult men’s collision sports such as rugby union is lacking.ObjectiveTo evaluate the efficacy of a movement control injury prevention exercise programme for reducing match injuries in adult men’s community rugby union players.Methods856 clubs were invited to participate in this prospective cluster randomised (single-blind) controlled trial where clubs were the unit of randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 38 publications
(39 reference statements)
4
98
0
1
Order By: Relevance
“…Attwood et al 5 however, mention that the sample size calculation was adjusted for a cluster coefficient (between-cluster coefficient of variation which is closely related to intracluster correlation coefficient) of 0.26. Also, they used generalised estimating equations along with a Pearson χ 2 scaling parameter to account for design effect.…”
Section: Design Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…Attwood et al 5 however, mention that the sample size calculation was adjusted for a cluster coefficient (between-cluster coefficient of variation which is closely related to intracluster correlation coefficient) of 0.26. Also, they used generalised estimating equations along with a Pearson χ 2 scaling parameter to account for design effect.…”
Section: Design Effectmentioning
confidence: 99%
“…The risk of random confounding is generally greater in cluster randomised trials than individual randomised trials as the number of clusters is often small 3. Both Hislop et al 4 and Attwood et al 5 papers presented the baseline characteristics of participants in table 1, but they did not adjust for non-negligible imbalances in some baseline characteristics in their analysis 9. Confusingly, Hislop et al 4 paper reported p values for baseline comparisons (some of which were significant at 5% level), a common misuse of p values in the randomised trial literature.…”
Section: Adjustment For Baseline Imbalancementioning
confidence: 99%
See 3 more Smart Citations